Progress in surface plasmon and other resonance biosensors for biomedical applications - Kamal Eddin, Faten Bashar; Fan, Houxin; Liu, Zhenchao; Donati, Paolo; Amin, Youssef; Fen, Yap Wing; Liang, Junbo; Pompa, Pier Paolo; He, Sailing (John Wiley and Sons, 2025)
In today's technologically advanced era, the demand for swift and precise analyses spans scientific research and industrial applications alike. Surface plasmon resonance (SPR) technology has surged in popularity, due to its real-time measurement capabilities with exceptional sensitivity and label-free operation. These attributes have propelled SPR into prominence across diverse fields including medical diagnostics, pharmaceuticals, food safety, and environmental monitoring of hazardous compounds. Here the key principles behind SPR are delved, and the workings of SPR-based sensors are elucidated. Additionally, the latest advancements in SPR biosensors tailored for detecting a variety of analytes, with a focus on dopamine (DA) and α-synuclein, which hold particular significance in the context of neurological disorders, are examined. Here potential breakthroughs of SPR technology are discussed, thanks to the integration with nanomaterials, lab-on-a-chip devices, multiplexing formats, and machine learning. Finally, new resonance modes are discussed based on subwavelength structures leveraging guided mode resonance (GMR), surface lattice resonance (SLR), and bound state in the continuum (BIC) mode resonance and their potential applications, particularly in nonplasmonic refractive index biosensors.